Estimating Historical Landfill Quantities to Predict Methane Emissions - LYONS, SEAN; TOL, RICHARD (ESRI, 2009)
We estimate Irish historical landfill quantities from 1960 -2008 and Irish methane emissions from 1968-2006. A model is constructed in which waste generation is a function of income, price of waste disposal and, household economies of scale. A transformation ratio of waste to methane is also included in the methane emissions model. Our results contrast significantly with the Irish Environmental Protection Agency's (EPA) figures due to the differences in the underlying assumptions. The EPA's waste generation and methane emission figures are larger than our estimates from the early 1990s onwards. Projections of the distance to target show that the EPA overestimates the required policy effort.
PUBLISHED
Keywords: Economics; Methane emissions; Landfill